2018
DOI: 10.3389/fmed.2018.00096
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antimicrobials for the Treatment of Clostridium difficile Infection

Abstract: The current picture of Clostridium difficile infection (CDI) is alarming with a mortality rate ranging between 3% and 15% and a CDI recurrence rate ranging from 12% to 40%. Despite the great efforts made over the past 10 years to face the CDI burden, there are still gray areas in our knowledge on CDI management. The traditional anti-CDI antimicrobials are not always adequate in addressing the current needs in CDI management. The aim of our review is to give an update on novel antimicrobials for the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 166 publications
0
43
0
2
Order By: Relevance
“…A phase II trial, started in 2015, showed higher clinical response rates than vancomycin. However, higher recurrence rates than vancomycin were also reported [ 21 ]. Thus, LFF571 was unfortunately discontinued from clinical development for CDI in 2019.…”
Section: Resultsmentioning
confidence: 99%
“…A phase II trial, started in 2015, showed higher clinical response rates than vancomycin. However, higher recurrence rates than vancomycin were also reported [ 21 ]. Thus, LFF571 was unfortunately discontinued from clinical development for CDI in 2019.…”
Section: Resultsmentioning
confidence: 99%
“…In order to mitigate these risks, meticulous donor screening has been adopted so far, including the check for the absence of viruses and other pathogens in the donor microbiota. At present, live microbiota preparations are in development to obtain the beneficial effect of FMT with a more controlled and regulated product [150].…”
Section: Non-traditional Approaches Against Mdr K Pneumoniae Futumentioning
confidence: 99%
“…Most of the AMPs that continue in clinical trials are for topical use. The following examples represent promising AMPs that have undergone clinical trials with different applications: OP-145 completed Phase II [40,[42][43][44], two AMPs targeting C. difficile, surotomycin which was discontinued after two Phase III studies [45][46][47] and NVB-302, has completed Phase I [40,[48][49][50].…”
Section: Peptides (Amps) and Peptidomimeticsmentioning
confidence: 99%